A comparative approach to understanding the ovule, seed, and fruit development in Bulbostylis (Cyperaceae : Cyperoideae : Abildgaardieae) - Reutemann, Andrea Guadalupe (2022)
Fil: Reutemann, Andrea Guadalupe. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencias Agropecuarias del Litoral; Argentina.